2019
DOI: 10.1158/1078-0432.ccr-19-0433
|View full text |Cite
|
Sign up to set email alerts
|

The Folate Pathway Inhibitor Pemetrexed Pleiotropically Enhances Effects of Cancer Immunotherapy

Abstract: Purpose: Combination strategies leveraging chemotherapeutic agents and immunotherapy have held the promise as a method to improve benefit for patients with cancer. However, most chemotherapies have detrimental effects on immune homeostasis and differ in their ability to induce immunogenic cell death (ICD). The approval of pemetrexed and carboplatin with anti-PD-1 (pembrolizumab) for treatment of non-small cell lung cancer represents the first approved chemotherapy and immunotherapy combination. Although the cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 45 publications
(53 reference statements)
5
76
0
Order By: Relevance
“…Interestingly, a recent study described enhanced immune control of tumors with combination TS inhibitor (pemetrexed) and anti-PD-L1 blockade, with clear evidence of heightened T cell priming, increased intratumoral leukocytes, and a greater T cell inflamed phenotype (Schaer et al, 2019). Our results are consistent with their observations of tumor immunogenic cell death, and higher levels of MHC class I on transformed cells may provide greater sources of tumor specific antigens.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a recent study described enhanced immune control of tumors with combination TS inhibitor (pemetrexed) and anti-PD-L1 blockade, with clear evidence of heightened T cell priming, increased intratumoral leukocytes, and a greater T cell inflamed phenotype (Schaer et al, 2019). Our results are consistent with their observations of tumor immunogenic cell death, and higher levels of MHC class I on transformed cells may provide greater sources of tumor specific antigens.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with recent findings showing that pemetrexed treatment in murine syngeneic colon tumor models (MC38 and Colon 26) activated T cells, inducing an inflamed phenotype, and that the addiction of an anti PD-L1 antibody improved the anti-tumor properties of the anti-folate compound [27].…”
Section: Discussionsupporting
confidence: 93%
“…In the present patient, first-line pemetrexed therapy may have contributed to the onset of alectinib-induced IHA. Cases of rheumatoid arthritis induced by pemetrexed therapy have been reported (11), and recent investigations have demonstrated that pemetrexed promotes lymphocyte activation (12). For this reason, first-line pemetrexed therapy probably induced autoantibody production and caused alectinibinduced IHA despite pemetrexed discontinuation.…”
Section: Discussionmentioning
confidence: 99%